Developing the Prospective Teachers' Cultural Competence by Means of the Museum Studies... - Z. U. Kolokolnikova; O. V. Lobanova; Y. N. Yakovleva (Russian State Vocational Pedagogical University, 2015)
The paper explores the cultural competence development in compliance with the new educational standards and regarding the pedagogic students. The above competence formation requires the complex approach and combination of both curricular and extracurricular educational forms. The research is aimed at demonstrating the opportunities of the museum teaching in the higher pedagogic schools as the effective means for developing the competence in question. The paper denotes the concepts of cultural educational activities and regional cultural educational environment, defines the components of the cultural educational competence, and describes the authors' teaching experience in the above competence formation related to the museum activity. The author carried out the experiment at Lesosibirsky Pedagogical Institute - the affiliate of Siberian Federal University; in the course of the History of Pedagogy and Education the students collected, explored and prepared the information for the Museum of the History of Education Development in Russia. The method of phased planning was applied to preparation of the museum exhibition, including the organizational, research, expositional and expert stages; the traditional pedagogic research methods of observation, questionnaires, analysis, etc. were applied in the course of the experiment. The research materials can be used by the teachers of the History of Pedagogy, heads of educational institutions and museum organizers.